LncRNA HCP5 Induces Gastric Cancer Cell Proliferation, Invasion, and EMT Processes Through the miR-186-5p/WNT5A Axis Under Hypoxia - Gao, Ming; Liu, Liying; Yang, Yudan; Li, Mengyi; Ma, Qingqing; Chang, Zhiwei (Frontiers in Cell and Developmental Biology, 2021)
Objective To experimentally determine the involvement and mechanism of long non-coding RNA (lncRNA) HCP5 in the development of gastric cancer (GC). Methods Detection of HCP5, miR-186-5p, and WNT5A expression in clinical GC tissues and adjacent healthy tissues was performed, followed by Pearson correlation analysis. BGC-823 and AGS cells, with interferences of HCP5, miR-186-5p, and WNT5A, were cultured under hypoxia. MTT, colony formation assay, Caspase-3 activity assay, and transwell assay were applied for the determination of cell proliferation, viability, apoptosis, and invasion, respectively. Expressions of WNT5A and protein markers of epithelial-mesenchymal transition (EMT) in cells were detected by western blotting. And the binding of HCP5 and WNT5A to miR-186-5p was validated using dual-luciferase reporter assay. Results In GC tissues, an increase in HCP5 and WNT5A expressions and a reduction in miR-186-5p expression were found, and the negative correlation between miR-186-5p and HCP5/WNT5A was proven. Subsequently, under hypoxia, an increase in HCP5 and WNT5A expressions and a decrease in miR-186-5p expression in GC cells were confirmed. In addition, in GC cells under hypoxia, the inhibition of HCP5 suppressed cell biological activity and EMT, while the inhibition of miR-186-5p or the overexpression of WNT5A led to the opposite changes. Conclusion An upregulation of WNT5A expression by HCP5 competitively binding to miR-186-5p promotes GC cell development.